2020
DOI: 10.1186/s40798-020-00260-z
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reliability of the One-Repetition Maximum (1RM) Strength Assessment: a Systematic Review

Abstract: Background The test–retest reliability of the one-repetition maximum (1RM) test varies across different studies. Given the inconsistent findings, it is unclear what the true reliability of the 1RM test is, and to what extent it is affected by measurement-related factors, such as exercise selection for the test, the number of familiarization trials and resistance training experience. Objectives The aim of this paper was to review studies that investigated the reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
163
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(178 citation statements)
references
References 68 publications
6
163
1
8
Order By: Relevance
“…Significant differences were also found when comparing the second and third sessions, with higher values for peak velocity, mean velocity, and mean power at 30% of 1RM recorded in the second session. These results seem counterintuitive, as one might expect to observe a better performance in subsequent testing, as observed for weight lifted in the 1RM test (Grgic et al, 2020). Banyard et al (2017) demonstrated that there are changes in the force-velocity relationship and its ability to predict 1RM in the back squat exercise across a week of training, even though the actual 1RM stayed relatively stable.…”
Section: Discussionmentioning
confidence: 91%
“…Significant differences were also found when comparing the second and third sessions, with higher values for peak velocity, mean velocity, and mean power at 30% of 1RM recorded in the second session. These results seem counterintuitive, as one might expect to observe a better performance in subsequent testing, as observed for weight lifted in the 1RM test (Grgic et al, 2020). Banyard et al (2017) demonstrated that there are changes in the force-velocity relationship and its ability to predict 1RM in the back squat exercise across a week of training, even though the actual 1RM stayed relatively stable.…”
Section: Discussionmentioning
confidence: 91%
“…Since the 1RM test and the sets until muscular failure were not a usual practice for participants, 3 weeks before the onset of the experimental trials, two familiarization sessions separated by 1 week were performed, in order to restrict learning effects during the experiment and decrease the risk of injury [ 32 ]. In each familiarization session, participants arrived at the laboratory at the same time of day and performed a standardized warm-up.…”
Section: Methodsmentioning
confidence: 99%
“…All repetitions were performed without bouncing the bar off the chest, without intentionally pausing at the transition between the negative and positive work, and without raising the hips off the bench. The 1RM test has goodto-excellent test-retest reliability (Grgic et al, 2020).…”
Section: Standard Bar One-repetition Maximum Strength Testmentioning
confidence: 99%